Effect of elevated CO2 concentration on microalgal communities in Antarctic pack ice. (September 2016) - Coad, Thomas; McMinn, Andrew; Nomura, Daiki; Martin, Andrew
Abstract: Increased anthropogenic CO2 emissions are causing changes to oceanic pH and CO2 concentrations that will impact many marine organisms, including microalgae. Phytoplankton taxa have shown mixed responses to these changes with some doing well while others have been adversely affected. Here, the photosynthetic response of sea-ice algal communities from Antarctic pack ice (brine and infiltration microbial communities) to a range of CO2 concentrations (400 ppm to 11, 000 ppm in brine algae experiments, 400 ppm to 20, 000 ppm in the infiltration ice algae experiment) was investigated. Incubations were conducted as part of the Sea-Ice Physics and Ecosystem Experiment II (SIPEX-2) voyage, in the austral spring (September–November), 2012. In the brine incubations, maximum quantum yield ( Fv / Fm ) and relative electron transfer rate ( rETRmax ) were highest at ambient and 0.049% (experiment 1) and 0.19% (experiment 2) CO2 concentrations, although, Fv / Fm was consistently between 0.53±0.10–0.68±0.01 across all treatments in both experiments. Highest rETRmax was exhibited by brine cultures exposed to ambient CO2 concentrations (60.15). In a third experiment infiltration ice algal communities were allowed to melt into seawater modified to simulate the changed pH and CO2 concentrations of future springtime ice-edge conditions. Ambient and 0.1% CO2 treatments had the highest growth rates and Fv / Fm values but only the highest CO2 concentration produced a significantly lower rETRmax . These experiments, conducted on natural Antarctic sea-ice algal communities, indicate a strong level of tolerance to elevated CO2 concentrations and suggest that these communities might not be adversely affected by predicted changes in CO2 concentration over the next century.